Patterns of community and species diversity in grassland vegetation of the southwestern Iberian System - Rodríguez Rojo, Maria Pilar; Sardinero, Santiago; Fernández-González, Federico (Lazaroa, 2013)
This paper reports a floristic and phytocenologic review of the mesic and dry grasslands of the southern Iberian System based on numerical and indicator species analysis. The crispness of classification was checked resulting in four main groups that classify grasslands in mesic (Molinio-Arrhenatheretea and Nardetea), semi-dry calcareous (Festuco-Brometea), dry calcareous (Sideritido fontquerianae-Arenarion aggregatae), and dry siliceous grasslands (Hieracio castellani-Plantaginion radicatae). DCA and CCA were performed on topographic parameters as explanatory variables of the community diversity and differences in variability between communities were also tested with ANOVA. Rock cover and slope best explained the differences in the floristic composition between the main vegetation groups, and for the discrimination of the dry cryoturbated grasslands (Sideritido-Arenarion aggregatae) from other types of grasslands, while altitude best discriminated some associations belonging to the same main vegetation group, such as the semi-dry grasslands (Cirsio microcephalae-Onobrychidetum hispanicae and Festuco andresmolinae-Brachypodietum phoenicoidis) and dry grasslands of upfrozen soils (Festucetum hystricis and Paronychio capitatae-Artemisietum lanatae). The exploration of the diagnostic species in combination with the topographic patterns of the community diversity brought out the phytosociological interpretation of transitional communities, like the case of Festucetum hystricis variant of Plantago maritima subsp. serpentina.